Development of the rodent prefrontal cortex: circuit formation, plasticity, and impacts of early life stress - Chen, Xinyi; Kim, Yuri; Kawaguchi, Daichi (Frontiers in Neural Circuits, 2025)
The prefrontal cortex (PFC), located at the anterior region of the cerebral cortex, is a multimodal association cortex essential for higher-order brain functions, including decision-making, attentional control, memory processing, and regulation of social behavior. Structural, circuit-level, and functional abnormalities in the PFC are often associated with neurodevelopmental disorders. Here, we review recent findings on the postnatal development of the PFC, with a particular emphasis on rodent studies, to elucidate how its structural and circuit properties are established during critical developmental windows and how these processes influence adult behaviors. Recent evidence also highlights the lasting effects of early life stress on the PFC structure, connectivity, and function. We explore potential mechanisms underlying these stress-induced alterations, with a focus on epigenetic regulation and its implications for PFC maturation and neurodevelopmental disorders. By integrating these insights, this review provides an overview of the developmental processes shaping the PFC and their implications for brain health and disease.